Comparative ovarian microarray analysis of juvenile hormone‐responsive genes in water flea Daphnia magna: potential targets for toxicity. Issue 3 (24th August 2016) - Toyota, Kenji; Williams, Timothy D.; Sato, Tomomi; Tatarazako, Norihisa; Iguchi, Taisen
Abstract: The freshwater zooplankton Daphnia magna has been extensively employed in chemical toxicity tests such as OECD Test Guidelines 202 and 211. Previously, it has been demonstrated that the treatment of juvenile hormones (JHs) or their analogues to female daphnids can induce male offspring production. Based on this finding, a rapid screening method for detection of chemicals with JH‐activity was recently developed using adult D. magna . This screening system determines whether a chemical has JH‐activity by investigating the male offspring inducibility. Although this is an efficient high‐throughput short‐term screening system, much remains to be discovered about JH‐responsive pathways in the ovary, and whether different JH‐activators act via the same mechanism. JH‐responsive genes in the ovary including developing oocytes are still largely undescribed. Here, we conducted comparative microarray analyses using ovaries from Daphnia magna treated with fenoxycarb (Fx; artificial JH agonist) or methyl farnesoate (MF; a putative innate JH in daphnids) to elucidate responses to JH agonists in the ovary, including developing oocytes, at a JH‐sensitive period for male sex determination. We demonstrate that induction of hemoglobin genes is a well‐conserved response to JH even in the ovary, and a potential adverse effect of JH agonist is suppression of vitellogenin gene expression, that might cause reduction of offspring number. This is the first report demonstrating different transcriptomics profiles from MF and an artificial JH agonist in D. magna ovary, improving understanding the tissue‐specific mode‐of‐action of JH. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A rapid screening method for the detection of chemicals with juvenile hormone (JH)‐activity was developed using adult Daphnia magna based on the phenomenon of induction of male offspring. However, JH‐responsive genes in the ovary are still largely undescribed. Here, we conducted comparative microarray analyses using ovaries treated with fenoxycarb (artificial JH agonist) or methyl farnesoate (a putative innate JH in daphnids) to elucidate responses to JH agonists in ovary, including developing oocytes, at a JH‐sensitive period for male sex determination.